Catheter-associated urinary infection in kidney post-transplant patients - Oliveira, Luiz Carlos de; Lucon, Antonio Marmo; Nahas, Willian Carlos; Ianhez, Luiz EEstevam; Arap, Sami (São Paulo Medical Journal, 2001)
CONTEXT: There is still controversy as to the use and dosageofantimicrobialprophylaxisoftheurinary infection associated with urethral catheterization in the post renal transplant period. OBJECTIVE: To determine whether patients develop urinary infection during short-term urethral catheterization after renal transplant with out routine antimicrobialprophylaxis. DESIGN: Prospective study. SETTING: Kidney Transplantation Unit. SAMPLE: 20 patients submitted to non-complicated kidneytransplant,with anormal urinary tract and no risk factors present regarding urinaryinfection. Aged 15 to 65 years. MAIN MEASUREMENTS: Before the transplant, material from the urethral meatus and urine were collected for culture. After the transplant, in the period during which the patient was with short- termurethralcatheterization(4to5days),material from the urethral meatus andurine from the bladder and the collecting bag were taken daily from all recipients for culture. RESULTS: There was a predominance of coagulase- negative Staphylococcus and S. viridans in the normal urethral meatus flora and in the first two days of urethral catheterization. After the second day, there was a predominance of E. coli and E. faecalis. Urinary infection did not occur during the period of urethral catheterization. In the follow uponlyonefemalepatient (7%) hadasymptomatic bacteriuria caused by E.coli after the withdrawal of the urethral catheter. CONCLUSIONS: Infection urinary does not occur during the period of urethral catheterization in kidneypost-transplantpatients.Thus,antimicrobial prophylaxisis not recommended for the sepatients to prevent urinary infection.